Utilization of Wilalondahi (Archidendron lucyi) as an Antihemorrhagic and Wound Healing Alternative Based on Ethnomedicine - Fitriani, Rezky Dwi; Naiym, Jannatun; Suhardin, Suhardin; Ali, Nur Fitriana Muhammad; Ramadan, Leski; Haris, Restu Nur Hasanah; Irwan, Irwan (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Hemorrhage is a leading cause of rapid death, particularly postpartum hemorrhage. One of the triggers is perineal wounds which, if not properly treated, can lead to complications such as bacterial infections. The people of Lalonggasumeeto, Southeast Sulawesi, empirically use Wilalondahi (Archidendron lucyi) bark to treat wounds. However, scientific evidence regarding its anti-inflammatory and wound-healing activities remains unavailable. This study evaluates the in vivo effect of Wilalondahi bark extract gel on the wound healing process in mice (Mus musculus). Methods included phytochemical screening, total flavonoid measurement, and observation of incision wounds. Parameters measured were healing duration, erythema, edema, and crusting. Results showed that the 96% ethanol extract of Wilalondahi bark contains a total flavonoid content of 65,67 mg QE/g. The extract demonstrated significant wound healing and anti-inflammatory activity (p < 0,05). The 15% concentration (P3) showed the most effective results, with wounds completely healed and crusts detached by day 9. Furthermore, the extract treatment was proven to effectively reduce inflammatory symptoms such as erythema and edema, showing comparable effectiveness to the positive control.